2017
DOI: 10.1111/psyg.12214
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and clinical correlates in older adults living in the community and in nursing homes in Macao

Abstract: Older Macanese adults had poorer scores on physical and social QOL domains than the general Hong Kong Chinese population. Their QOL was more strongly related to severe depressive symptoms, major medical conditions, and insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…This factor could probably influence their perceived mental health well-being. It was observed that a lower educational background was a predictor for a poor psychological QoL amongst the elderly, both in the community and in the NH study settings [25].…”
Section: Discussionmentioning
confidence: 94%
“…This factor could probably influence their perceived mental health well-being. It was observed that a lower educational background was a predictor for a poor psychological QoL amongst the elderly, both in the community and in the NH study settings [25].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, a study found better QoL of institutionalized elderly men compared to the non-institutionalized elderly in physical and psychological domains [15], which was attributed to the multidisciplinary professional team offering support and stimulus to the institutionalized elderly. Other studies did not find differences in the QoL between institutionalized elderly and non-institutionalized elderly [14,20]. Finally, divergent results, from different QoL questionnaire domains were observed between institutionalized and noninstitutionalized elderly [10,12,21,24].…”
Section: Introductionmentioning
confidence: 91%
“…Out of these 25 studies, 10 did not compare the QoL of institutionalized and non-institutionalized elderly; three used Likert scale or VAS for QoL evaluation; five were validation studies of the QoL questionnaire; and seven included participants with Alzheimer's disease, dementia, cognitive impairment or disability. Sixteen studies were included for the data extraction and qualitative synthesis [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and 12 for the quantitative synthesis [10,12,13,[16][17][18][20][21][22][23][24][25].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study was carried out from September 2015 to November 2016. 18 In Macau there are 20 nursing homes; we randomly selected 11 to participate in this study. In Guangzhou, only a large public nursing home with around 1200 older residents was included.…”
Section: Study Sitementioning
confidence: 99%